GSK-3β deletion in dentate gyrus excitatory neuron impairs synaptic plasticity and memory - Enjie Liu (Nature Portfolio, 2017)
Abstract Increasing evidence suggests that glycogen synthase kinase-3β (GSK-3β) plays a crucial role in neurodegenerative/psychiatric disorders, while pan-neural knockout of GSK-3β also shows detrimental effects. Currently, the function of GSK-3β in specific type of neurons is elusive. Here, we infused AAV-CaMKII-Cre-2A-eGFP into GSK-3βlox/lox mice to selectively delete the kinase in excitatory neurons of hippocampal dentate gyrus (DG), and studied the effects on cognitive/psychiatric behaviors and the molecular mechanisms. We found that mice with GSK-3β deletion in DG excitatory neurons displayed spatial and fear memory defects with an anti-anxiety behavior. Further studies demonstrated that GSK-3β deletion in DG subset inhibited hippocampal synaptic transmission and reduced levels of GluN1, GluN2A and GluN2B (NMDAR subunits), GluA1 (AMPAR subunit), PSD93 and drebrin (postsynaptic structural proteins), and synaptophysin (presynaptic protein). GSK-3β deletion also suppressed the activity-dependent neural activation and calcium/calmodulin-dependent protein kinase II (CaMKII)/CaMKIV-cAMP response element binding protein (CREB) signaling. Our data suggest that GSK-3β in hippocampal DG excitatory neurons is essential for maintaining synaptic plasticity and memory.